"Presenting Our Perspective": Recontextualizing Youths' Experiences of Hypercriminalization Through Media Production. (April 2019) - Smirnov, Natalia; Lam, Wan Shun Eva
In this study, we examine how youth use media production to represent, (de)legitimate, and reimagine their experiences of hypercriminalization—the pervasive complex of social practices such as racial profiling that position young men of color as "always-already criminal." We analyze two clips from a youth-produced news show called POPPYN, specifically a 2014 episode focusing on youth and the criminal justice system, using tools from recontextualization analysis and multimodal semiotics, which together allow us to index the substitutions, deletions, rearrangements, and additions of component elements of social practices. Through investigation of linguistic and multimodal processes that represent social actors, actions, and constructions of their legitimacy, this study demonstrates ways that media making can serve as a tool for youth of color to process and rewrite persistent hypercriminalizing positionings in more agentive and hopeful ways. We end by proposing implications for multimodal literacy practices and pedagogies.